A General Strategy for In Situ Growth of All‐Inorganic CsPbX3 (X = Br, I, and Cl) Perovskite Nanocrystals in Polymer Fibers toward Significantly Enhanced Water/Thermal Stabilities. Issue 15 (17th May 2018) - Liao, Hao; Guo, Shibo; Cao, Sheng; Wang, Lin; Gao, Fengmei; Yang, Zuobao; Zheng, Jinju; Yang, Weiyou
Abstract: Currently, all‐inorganic CsPbX3 (X = Br, I, and Cl) perovskites (IPs) are emerging as excellent candidate materials for exploring optoelectronic devices, due to their superior optical/electronic performances. However, their intrinsic poor stability greatly limits their practical applications. Here, a general strategy is reported for in situ growth of all‐inorganic perovskite nanocrystals (IPNCs) in polymer fibers with highly uniform size and spatial distribution, which is based on one‐step electrospinning of solutions containing IPs precursors and polymers. It is verified that the IPNCs of CsPbX3 can be uniformly encapsulated within the polymer fibers with finely tuned compositions, by rationally adjusting the ratios of PbX2 and CsX salts in the raw solutions. Consequently, the photoluminescence (PL) emissions of CsPbX3 @polymer fibers can be readily tuned to cover the whole visible range. The obtained CsPbBr3 @polymer fibers exhibit fundamentally improved water/thermal stabilities with a PL quantum yield (QY) of 48%. Their PL QY retains beyond 70% of its original value after being immersed in water for 192 h and maintains over 50% after being heated at 80 °C for 120 min. Furthermore, the light emitting diodes with high brightness based on CsPbBr3 @polymer fibers are constructed, suggesting their promising applications. Abstract : A general strategy based on one‐step electrospinning for in situ growth of CsPbX3 (X = Br, I, and Cl) nanocrystalys within polymer fibers with uniform size and spatial distribution is reported, which can be highly effective for significantly enhancing the stability of all‐inorganic perovskites against water and thermal.